Synthetic materials and the theory of international trade - Hufbauer, Gary Clyde (London: Duckworth, 1966)
The purpose of the book is to examine ,in the light of economic theory,both the pattern of national location in the synthetic materials industry,and the trade flows emerging from industry's development
Bibliography: p. [154]-160.
obn 25/01/2019
Loans
Keywords: Plastics industry and trade; Textile fibers, Synthetic